PEMANFAATAN SAMPAH PLASTIK DAN ORGANIK DALAM PEMBUATAN PAVING BLOCK MENGGUNAKAN MESIN PRESS - Ubaidillah, zacky; Sumarjo, Jojo; Widianto, Eri; Hanifi, Rizal (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2019)
Research has been done on the manufacture and testing of paving blocks with plastic and organic waste materials using a press machine. The purpose of this study is to determine the compressive strength of paving blocks and as a solution for handling waste around us. The results of manual making paving block research with 100% plastic waste, the highest value was 110.4 kg/cm2 and the lowest was 42.2 kg/cm2 and the highest organic mixture was 99.8 kg/cm2 and the lowest was 56.0 kg/cm2. Whereas in the masinal pembutan produce value with 100% plastic waste 113,9 kg/cm2 the lowest value 78,4 kg/cm2. Paving blocks with plastic waste materials are in accordance with SNI quality qualifications. Keywords: plastic waste, organic mixture, paving block, hard test press, machine press.